Analisis Komunikasi Efektif Karyawan Generasi Z pada Divisi Marketing Communication di Perusahaan Perbankan - Zidny Brilliantsyah; Rizki Firdausi Rachmadania; Roni Faslah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the Effective Communication of Generation Z Employees in the Marketing Communication Division of a Banking Company. This study uses a qualitative descriptive approach. In this study, a purposive sampling technique was used to select informants who fit the research focus, namely generation Z employees in the Marketing Communication division of PT Bank KB Indonesia Tbk who are directly involved in daily work communication activities. Based on these criteria, the researcher determined four informants consisting of one Marketing Communication Coordinator and two Marketing Communication Staff. The implementation of effective communication in the Marketing Communication division has been running quite well by applying the REACH communication principles, which include respect, empathy, audibility, clarity, and humility. This is evident in the mutual respect among employees, the ability to understand coworkers' perspectives, the use of various communication media, and openness in accepting criticism and admitting mistakes in the work communication process. The characteristics of generation Z have an influence on communication patterns in the work environment. Generation Z tends to have a more open, communicative communication style, and is easily adaptable to the use of digital technology in work communication activities. In addition, generation Z is also more active in conveying ideas and opinions in work discussions, thus supporting the creation of more dynamic work communication. Although work communication in the Marketing Communications division has been running quite well, several barriers remain that impact its effectiveness. These barriers include differences in perceptions regarding messages, unclear work instructions, and differences in communication styles between generations in the workplace.